The professional needs of the elementary school teachers in the district of Victoria, Tarlac. - Tabunda, Avelina S. 1922- (s.n., 1968)
This study attempts to discover the professional needs of elementary school teachers in Victoria, Tarlac through questionnaires, interview, and rating scale. The areas of Nature of the Learner and the Learning Process, Curriculum and Instruction, Measurement and Evaluation, Guidance and Research, School Administration and Supervision, and Human Relations were evaluated. Results show that professional needs of teachers from 1966-1967 were satisfied through demonstration teaching, workshops, seminars, work conferences, intervisitations, and classroom observations.